Competencies of the Rehabilitation Counselor to Work with Lesbian, Gay and Bisexual Clients (LGB) - Rivera-Colón, Raúl; Ramos-Reyes, Maximino; Vázquez-Ramos, Robinson (Revista Electrónica Educare, 2019)
Rehabilitation counselors must provide services to diverse populations including lesbian, gay and bisexual (LGB) individuals. This quantitative study of descriptive exploratory type auscultated the competencies of a group of rehabilitation counselors to work with the LGB population. The sample consisted of 118 rehabilitation counseling professionals who were recruited utilizing a convenience sampling technique. The instruments administered were a sociodemographic data questionnaire and the Sexual Orientation Counselor Competence Scale (SOCCS), (Bidell, 2005). Variables were analyzed with the Spearman t-test and correlation. The participants showed moderate competences in the subscales of the SOCCS (knowledge, skills, and attitudes) and in the overall average of the Scale. No statistically significant result was identified in terms of gender variables and the work scenario of the counselors. A statistically significant negative relationship was found between years of working experience in rehabilitation counseling, the skills and attitudes subscales. These results may be used for the development of continuing education programs for rehabilitation counselors with the aim of improving the well-being of their LGB clients.